2020
DOI: 10.1021/acs.langmuir.0c02736
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Membrane Fluidity to Control Interfacial Water Structure and Dynamics in Saturated and Unsaturated Phospholipid Vesicles

Abstract: The structure and dynamics of interfacial water in biological systems regulate the biochemical reactions. But, it is still enigmatic how the behavior of the interfacial water molecule is controlled. Here, we have investigated the effect of membrane fluidity on the structure and dynamics of interfacial water molecules in biologically relevant phopholipid vesicles. This study delineates that modulation of membrane fluidity through interlipid separation and unsaturation not only mitigate membrane rigidity but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In fact, our group and other groups previously have used C153 as a solvation and anisotropy probe in the phospholipid vesicle system and have concluded that C153 is located at the membrane or interface region rather than the water pool. 42,45,66,75 Coumarin dyes are very good markers of microenvironment polarity. Coumarin dyes have been extensively used to determine solvation dynamics due to its large Stokes shift, which is beneficial for comparison of two systems exhibiting small differences on the solvation dynamics time scale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, our group and other groups previously have used C153 as a solvation and anisotropy probe in the phospholipid vesicle system and have concluded that C153 is located at the membrane or interface region rather than the water pool. 42,45,66,75 Coumarin dyes are very good markers of microenvironment polarity. Coumarin dyes have been extensively used to determine solvation dynamics due to its large Stokes shift, which is beneficial for comparison of two systems exhibiting small differences on the solvation dynamics time scale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The femtosecond time-resolved upconversion data were collected in a commercially available fluorescence upconversion setup (Fluomax, IB Photonics) (Figure S1), in which a solid-state Ti-sapphire laser (Mai Tai HP, Spectra Physics) with a tunable range from 690 to 1040 nm was used as the laser source. , In our experiment, we used an 800 nm pulsed laser with a pulse width of 100 fs and a repetition rate of 80 MHz. In this setup, the fundamental 800 nm laser beam was focused onto a nonlinear β-barium borate (BBO) crystal to generate the frequency-doubled 400 nm visible lamp beam.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Although almost all liquid crystalline lipid bilayers undergo large molecular displacements, their intermolecular interactions are lipid specific [4][5][6][7]. In biological membranes, lipids are in constant motion-due to thermal energy-and their movements impact their physical properties, such as bilayer viscosity, energy and heat transfer, lipid diffusion, and overall morphology [8][9][10][11][12]. Importantly, lipid bilayers are the underlying structures of biological membranes and define the cell's extracellular and intracellular environments [13,14], and enable a range of biological processes [15].…”
Section: Introductionmentioning
confidence: 99%
“…By using phospholipid-based membrane mimetic models, it has been possible to show that RLs have the capability to influence membrane fluidity, a property highly dependent on phospholipid acyl chain length, saturation degree ( Hazel, 1995 ; Ernst, Ejsing, and Antonny, 2016 ; Sezgin et al, 2017 ; Fonseca et al, 2019 ; Mondal et al, 2020 ) and the concentration of sterols ( Hartmann, 1998 ; Piironen et al, 2000 ; Vance, 2000 ; Volkman, 2003 ). In particular, di-RLs are able to alter the lipid dynamics and lower the temperature of the gel-to-fluid phase transition ( Ortiz et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%